Asuhan Kebidanan Komprehensif Pada Ny. M Umur 37 Tahun Dengan Riwayat Pre Eklampsia Berat Dan Sectio Caesarea Di Puskesmas Kaliwadas Kabupaten Brebes Tahun 2023 - Naya Ainun Aprilia; Hafsah Hafsah; Sri Mulyani (Jurnal Anestesi, 2024)
According to the World Health Organization (WHO) in 2020 stated that the maternal mortality rate (MMR) due to pre-eclampsia is very high, every day 810 women die due to complications of pregnancy and childbirth and around 295 000 women die after childbirth or in the postpartum period while in Indonesia 6-15%. In Central Java 98.6 per 100,000KH, while in Brebes 536 cases and in Kaliwadas Health Center 6 cases. To provide comprehensive midwifery care services for pregnant women, delivery, newborn, postpartum, and family planning. This research used descriptive qualitative method with case study approach. Comprehensive Midwifery Care for Mrs. M aged 37 years with a history of severe preeclampsia and sectio caesarea using Varrney documentation management, SOAP and there are significant similarities. Comprehensive midwifery care for Mrs. M from pregnancy, up to family planning, and using Varrney's flow of thought with SOAP documentation, mother and baby in good condition.